Regendering Radegund? Fortunatus, Baudonivia and the Problem of Female Sanctity in Merovingian Gaul - Coates, Simon (Studies in church history, 1998)
In the prologue of her De vita sancti Radegundis, Baudonivia, an inhabitant of Radegund’s community of the Holy Cross at Poitiers, adopted a phrase from Venantius Fortunatus’ Vita Hilarii to express her unworthiness for the task: ‘I can as easily touch heaven with my fingers as perform the task you have imposed on me.’ Baudonivia, the first female hagiographer in Merovingian Gaul, was here drawing from the Life of a male saint to introduce her work. She was thus, like all hagiographers, not alone in her task. This was doubly the case, since immediately prior to the composition of her own work Venantius Fortunatus had himself composed a Vita of the saint. Radegund was thus a focus of both male and female interest. This paper will examine the two Lives from a gendered perspective, exploring the manner in which gender, a constructed rather than a physiological form of sexual differentiation, may illumine Radegund’s sanctity.